Determination of the phase transformation temperatures of the Fe-Co-Cu-Si system in the Fe-Rich corner by Thermal Analysis - Banda, W.; Georgalli, G.; Lang, C.; Eksteen, Jacques (TMS Publications, 2008)
A combination of differential thermal analysis (DTA) and drop-quench experiments were conducted on the Fe-Co-Cu-Si system within the compositional range of the ferrocobalt produced in the smelting of copper waste slags to recover copper and cobalt. In the temperatures investigated (>1000°C), the system was found to contain two solid solutions, namely, a- and ?-Fe. At temperatures close to 1100°C, a peritectic reaction resulted in a Cu-rich liquid in equilibrium with the solid solutions. Just below the liquidus temperature the ?-Fe was found to transform allotropically to a-Fe, which remained in equilibrium with the Cu-rich liquid. At the liquidus temperature a Fe-rich liquid phase was formed by a monotectic reaction between the Cu-rich liquid and the a-Fe. The liquidus temperature of the Fe-Co-Cu-Si system was found to decrease with increasing Si content. In the range studies (1 to 5.5 pct Si) the liquidus temperature decreased by 70°C